Smart destinations as method to rethink tourism marketing: a simplified method that any business or destination con implement it! - Jardim, Fernando Nahat (2019)
The present academic work seeks to contribute to the existing discussion about tourism marketing in Brazil, relating it to modern tourism development frameworks and understanding key issues of tourism development in the country. Through literature review, surveys and tests a simplified tourism development framework model was developed. Then, in deep interviews with tourism specialists were conducted in order to better understand that industry and to validate the first version of the model. After the interviews, all the data was analysed, and it was possible to understand the main problems regarding tourism development in Brazil and what should be done in order to put in place a modern and technological tourism development framework. Finally, the prior model was evolved to the final version of the simplified tourism development framework, which now addresses the Brazilian tourism key industry issues, such as the creation of a local governance, continuity of public policies, the non-digitalized trade sector and their old business mindset, and many others. This simplified framework would allow any manager without any previous knowledge in tourism / technology to implement modern, digital and technological methods that are necessary in order to succeed in their tourism strategies.